Evaluación de las principales características poblacionales de Mauritia Flexuosa frente al cambio climático en el área de conservación municipal Asociación Hídrica Aguajal Renacal del Alto Mayo. - Novoa Ramírez, Jean Yves (2010)
This paper evaluates scientific and institutional aspects of climate change and population characteristics of Mauritia flexuosa in the Conservation Area Municipal Water Association Aguajal - Renacal the Alto Mayo. In the first section of the paper is the problem statement, drawing general objectives, such as assessment of population characteristics of the Mauritia flexuosa climate change with specific activities were the identification of environmental factors that would interact with biological processes of the water source, later determined the degree of vulnerability analysis space – time. In this section reviews the state of knowledge of terms such as aguajales, climate change, greenhouse gases, changing land use, to name the relevant, it should be mentioned that until now there is a document of similar import. In the second section to determine a viable methodology for this evaluation was a comprehensive review of the literature found material as AHARAM Management Plan, Management Plans Aguaje in protected natural areas and Economic Valuation of Environmental Benefits in Sustainable Management Wetlands, but no contribution to design an evaluation of this nature, in that sense, the proposal is new, as the Intergovernmental Panel on Climate Change recommended as a strategy for reducing vulnerability to climate change is the regionalization of weather events such as early warning networks to potential climate change events. Towards this direction would be providing this assessment. In the third section presents the results with respect to temperature shows a variation of (+/-) 0.53 ° C and 0.67 ° C, with average temperatures of 23 and 23.5 ° C in Pueblo Libre station and Valley Conquest unlike the basin where the 2020 comes to a temperature increase of 1 - 1.2 ° C. With regard to the precipitation has a record of 1278.1 and 1276.3mm with positive trends of 21 and 31%. The increased vulnerability that comes through the population characteristics of Mauritia flexuosa, is due to land use change that comes through this town, causing a possible edge effect, this largely due to the selective extraction (timber products of high commercial value), extension predominantly agricultural frontier of rice 67.9% and 32% in the Valley of the Conquest and Pueblo Libre and the mishandling of the water source for use in marketing and post harvest the palm tree is female grave goods and services decline as it breaks the food chain and biogeochemical processes (carbon cycle) rather than the ability to act as sinks of greenhouse gases, it is found that a hectare of this crop annually, has the ability to capture carbon 600Tn. Mauritia flexuosa populations are very complex and dynamic ecosystems with strong interaction between them. While the results obtained in this paper should motivate the academic community, professionals and public and private institutions in the investigation of these dynamics and their interactions. Daring to define some lines of research such as: Defining carbon fluxes, Environmental Economic Valuation Using Indirect Vs Direct Use of the ecosystem, Implementation of Avoided Deforestation Proposal. The recommendation of this document goes towards the creation of the Regional Intergovernmental Panel made up of different sectors and levels of government with guidelines for action to improve people's capabilities in resource management, environmental education, implementation strategies management plan also negotiate with the relevant bodies for recognition as a RAMSAR site Aguajal Water Partnership – Upper Ranaca May between the activities aimed at climate change adaptation.